Associação Brasileira de Hematologia, Hemoterapia e Terapia Celular Consensus on genetically modified cells. III: anti-CD19 CAR-T cell therapy for patients with non-Hodgkin lymphoma - Alvaro J. Alencar (Elsevier, 2021)
The treatment and evolution of B-cell non-Hodgkin lymphoma (B-NHL) has undergone important changes in the last years with the emergence of targeted therapies, such as monoclonal antibodies, small molecules, antibody-drug conjugates, and bispecific antibodies. Nevertheless, a significant portion of patients remains refractory or relapsed (R/R) to the new therapeutic modalities, representing thus an unmet medical need. The use of CAR-T cells for the treatment of B-NHL patients has shown to be a promising therapy with impressive results in patients with R/R disease. The expectations are as high as the imminent approval of CAR-T cell therapy in Brazil, which it is expected to impact the prognosis of R/R B-NHL. The aim of this manuscript is to offer a consensus of specialists in the field of onco-hematology and cellular therapy, working in Brazil and United States, in order to discuss and offer recommendations in the present setting of the use of CAR-T cells for patients with B-NHL.